2018
DOI: 10.1017/s0029665118000046
|View full text |Cite
|
Sign up to set email alerts
|

A window beneath the skin: how computed tomography assessment of body composition can assist in the identification of hidden wasting conditions in oncology that profoundly impact outcomes

Abstract: Advancements in image-based technologies and body composition research over the past decade has led to increased understanding of the importance of muscle abnormalities, such as low muscle mass (sarcopenia), and more recently low muscle attenuation (MA), as important prognostic indicators of unfavourable outcomes in patients with cancer. Muscle abnormalities can be highly prevalent in patients with cancer (ranging between 10 and 90 %), depending on the cohort under investigation and diagnostic criteria used. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 176 publications
4
62
0
Order By: Relevance
“…Thus, a vicious cycle develops; cachexia reduces the possibility of using cytotoxic agents, thus leading to disease progression, and this in turn promotes the development of resistant cachexia . Most research to date has focused on treating muscle depletion as part of the cachexia syndrome using nutritional, exercise, and pharmacological interventions; however, these single‐agent therapies have not provided promising results …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a vicious cycle develops; cachexia reduces the possibility of using cytotoxic agents, thus leading to disease progression, and this in turn promotes the development of resistant cachexia . Most research to date has focused on treating muscle depletion as part of the cachexia syndrome using nutritional, exercise, and pharmacological interventions; however, these single‐agent therapies have not provided promising results …”
Section: Discussionmentioning
confidence: 99%
“…43 Most research to date has focused on treating muscle depletion as part of the cachexia syndrome using nutritional, exercise, and pharmacological interventions; however, these single-agent therapies have not provided promising results. 49 It is important to highlight that different instruments in literature for assessing loss of muscle mass can produce a relative variability in frequency of sarcopenia and cachexia, and there are multiple methods of adjusting the result for height or for BMI. 50 Recently, Blauwhoff-Buskermolen et al 51 found a large variation of prevalence of low muscle mass (13% to 93%) with different techniques (anthropometry, CT, and bioelectrical impedance) in cancer patients, and it has repercussion in diagnosis of cachexia and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the increased number of patients presenting in an overweight or obese state in the developed world, the use of simple weight loss and BMI as a prognostic indicator has been questioned . The ability to use routine computed tomography (CT) scans to measure body composition, in particular skeletal muscle, has resulted in a marked increase in interest in using skeletal muscle index (SMI) and skeletal muscle density (SMD) to predict outcomes in patients with cancer, particularly in CRC …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] The ability to use routine computed tomography (CT) scans to measure body composition, in particular skeletal muscle, has resulted in a marked increase in interest in using skeletal muscle index (SMI) and skeletal muscle density (SMD) to predict outcomes in patients with cancer, particularly in CRC. 8 There is evidence supporting a disproportionate loss of skeletal muscle tissue to be an independent prognostic factor for both cancer specific and overall survival in patients with CRC. 9 Specifically, muscle loss has been associated with poor treatment tolerance and efficacy, 10 worse quality of life, and increased morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews that summarized the appraisement of SM radiodensity by CT (Aubrey et al , 2014; Daly, Prado, & Ryan, 2018; Kazemi‐Bajestani, Mazurak, & Baracos, 2016) did not explore extensively the topics related to the methodological approach in different populations.…”
Section: Introductionmentioning
confidence: 99%